2007
DOI: 10.1590/s1413-70542007000400032
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição da umidade num perfil de solo irrigado por gotejamento superficial e subsuperficial

Abstract: Conduziu-se o presente trabalho com o objetivo de avaliar a distribuição de água no perfil de um Latossolo cultivado com mamoeiro do grupo Formosa, irrigado por dois gotejadores por planta instalados a 0,30 m da mesma. Usou-se gotejamento superficial com emissores de vazão de 3,75 L.h-1 e subsuperficial com emissores de vazão foi 2 L.h-1 a 0,25 m de profundidade. Os valores de umidades foram obtidos por meio de sondas de TDR instaladas e distribuídas em perfis de solo. As leituras foram realizadas em intervalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
0
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
2
0
0
3
Order By: Relevance
“…This result corroborates with study by SOUZA et al (2007), which is found that occurred leaching of the solution and stabilization of the wet surface area on sandy soil when applied frequent irrigation depth, after a period of 6 hours and a flow rate of 1 L h -1 . Different results were observed by BARROS et al (2009), who concluded that the high frequency irrigation, in Red Nitosols did not promote stabilization of the wetted area being the emitter positioned on surface or 0.10 m depth.…”
Section: Resultssupporting
confidence: 92%
“…This result corroborates with study by SOUZA et al (2007), which is found that occurred leaching of the solution and stabilization of the wet surface area on sandy soil when applied frequent irrigation depth, after a period of 6 hours and a flow rate of 1 L h -1 . Different results were observed by BARROS et al (2009), who concluded that the high frequency irrigation, in Red Nitosols did not promote stabilization of the wetted area being the emitter positioned on surface or 0.10 m depth.…”
Section: Resultssupporting
confidence: 92%
“…This can be explained by the fact that water tends to move to the soil surface before the infiltration-percolation process begins. Analyzing Figures 1A and 2A, it is observed that the bulb radius was smaller than its depth; similar situation was observed by Souza et al (2007). In Figure 1A, it is verified that the radial distance achieved by the wetted surface was 18 cm, wherein Rivera (2004) and Nogueira et al (2000), applying water by surface drip, obtained radial values of 35 and 25 cm, respectively.…”
Section: Resultssupporting
confidence: 76%
“…Uma variante ao sistema de gotejamento tradicional é o gotejamento subsuperficial. De acordo com Souza et al (2007) o sistema de irrigação por gotejamento subsuperficial apresenta algumas vantagens em relação ao superficial, tais como: aumento substancial na eficiência de irrigação e maior durabilidade e a redução da área de evaporação de água a partir da superfície do solo. Entretanto, esta variante do gotejamento pode aumentar o risco potencial de entupimento devido à entrada de partículas de solo e/ou intrusão radicular nos emissores.…”
Section: Introductionunclassified